Protective effect of topical Cordia verbenacea in a rat periodontitis model: immune-inflammatory, antibacterial and morphometric assays - Pimentel Suzana; Barrella Guilherme; Casarin Renato Corrêa; Cirano Fabiano; Casati Márcio; Foglio Mary; Figueira Glyn; Ribeiro Fernanda (BMC, 2012)
Abstract Background This study evaluated the effects of C. verbenacea essential oil topically administered in a rat periodontitis model. Methods Periodontitis was induced on rats in one of the mandibular first molars assigned to receive a ligature. Animals were randomly divided into two groups: a) non-treatment group (NT) (n = 18): animals received 1mL of vehicle; b) C. verbenacea group (C.v.) (n = 18): animals received 5mg/Kg of essential oils isolated from C. verbenacea. The therapies were administered topically 3 times daily for 11 days. Then, the specimens were processed for morphometric analysis of bone loss. The ligatures were used for microbiological assessment of the presence of Aggregatibacter actinomycetemcomitans, Tannerella forsythia and Porphyromonas gingivalis using PCR. The gingival tissue was collected to Elisa assay of interleukin (IL)-1α and IL-10 levels. Results Bone loss was inhibited by C. verbenacea when compared to the NT group (p < 0.05). A decrease in the levels of IL-1α and increase in the IL-10 amounts was observed in the C.v. group as compared to NT group (p < 0.05). A lower frequency of P. gingivalis was found in C.v. group (p < 0.05). Conclusion C. verbenacea essential oil topically administered diminished alveolar bone resorption, promoting a positive local imbalance in the pro/anti-inflammatory system and reducing the frequency of detection of P. gingivalis.